Addressing the burden of mental, neurological, and substance use disorders: key messages from Disease Control Priorities, 3rd edition. Issue 10028 (16th April 2016) - Patel, Vikram; Chisholm, Dan; Parikh, Rachana; Charlson, Fiona J; Degenhardt, Louisa; Dua, Tarun; Ferrari, Alize J; Hyman, Steve; Laxminarayan, Ramanan; Levin, Carol; Lund, Crick; Medina Mora, María Elena; et al.
Summary: The burden of mental, neurological, and substance use (MNS) disorders increased by 41% between 1990 and 2010 and now accounts for one in every 10 lost years of health globally. This sobering statistic does not take into account the substantial excess mortality associated with these disorders or the social and economic consequences of MNS disorders on affected persons, their caregivers, and society. A wide variety of effective interventions, including drugs, psychological treatments, and social interventions, can prevent and treat MNS disorders. At the population-level platform of service delivery, best practices include legislative measures to restrict access to means of self-harm or suicide and to reduce the availability of and demand for alcohol. At the community-level platform, best practices include life-skills training in schools to build social and emotional competencies. At the health-care-level platform, we identify three delivery channels. Two of these delivery channels are especially relevant from a public health perspective: self-management (eg, web-based psychological therapy for depression and anxiety disorders) and primary care and community outreach (eg, non-specialist health worker delivering psychological and pharmacological management of selected disorders). The third delivery channel, hospital care, which includes specialist services for MNS disorders and first-level hospitals providing other types of services (such as general medicine, HIV, or paediatric care), play an important part for a smaller proportion of cases with severe, refractory, or emergency presentations and for the integration of mental health care in other health-care channels, respectively. The costs of providing a significantly scaled up package of specified cost-effective interventions for prioritised MNS disorders in low-income and lower-middle-income countries is estimated at US$3–4 per head of population per year. Since a substantial proportion of MNS disorders run a chronic and disabling course and adversely affect household welfare, intervention costs should largely be met by government through increased resource allocation and financial protection measures (rather than leaving households to pay out-of-pocket). Moreover, a policy of moving towards universal public finance can also be expected to lead to a far more equitable allocation of public health resources across income groups. Despite this evidence, less than 1% of development assistance for health and government spending on health in low-income and middle-income countries is allocated to the care of people with these disorders. Achieving the health gains associated with prioritised interventions will require not just financial resources, but committed and sustained efforts to address a range of other barriers (such as paucity of human resources, weak governance, and stigma). Ultimately, the goal is to massively increase opportunities for people with MNS disorders to access services without the prospect of discrimination or impoverishment and with the hope of attaining optimal health and social outcomes.